Qualitative study of views of health professionals and patients on guided self management plans for asthma. Issue 7275 (16th December 2000) - Jones, Alan; Pill, Roisin; Adams, Stephanie
Abstract: Objectives: To explore the views held by general practitioners, practice nurses, and patients about the role of guided self management plans in asthma care. Design: Qualitative study using nine focus groups that each met on two occasions. Setting: South Wales. Subjects: 13 asthma nurses, 11 general practitioners (six with an interest in asthma), and 32 patients (13 adults compliant with treatment, 12 non-compliant adults, and seven teenagers). Results: Neither health professionals nor patients were enthusiastic about guided self management plans, and, although for different reasons, almost all participants were ambivalent about their usefulness or relevance. Most professionals opposed their use. Few patients reported sustained use, and most felt that plans were largely irrelevant to them. The attitudes associated with these views reflect the gulf between the professionals' concept of the "responsible asthma patient" and the patients' view. Conclusions: Attempts to introduce self guided management plans in primary care are unlikely to be successful. A more patient centred, patient negotiated plan is needed for asthma care in the community.